A revision of Leptogium species with spherical-celled hairs (section Mallotium p.p.) - Kitaura, Marcos J. [UNESP]; Marcelli, Marcelo P. (Amer Bryological Lichenological Soc Inc, 2013)
The group of Leptogium species with spherical-celled hairs (i.e., sect Mallotium) is revised and identification keys for fertile and sterile specimens are provided based on morphological and anatomical characteristics. Apothecial tissues are important in species differentiation and are related to the type of columnar hyphae of the thallus. Mallotium species can be readily differentiated by the surface morphology, architecture of the hairs, the type and distribution of isidia and lobules, the columnar hyphae, and features of apothecial tissues. The thallus of L. inflexum lacks marginal lacinulae, but was retained in synonymy with L. burgessii, whereas L. ethiopicum was distinguished from L. burgessii. Leptogium nylanderi is a new name for L. inflexum var. isidiosulum. The new species L. mantiqueirense is described from southeastern Brazil.
Keywords: Collemataceae; collar; true isidium; colloplectenchyma; lichen taxonomy; scleroplectenchyma